Upaya Guru Dalam Membangun Literasi Baca Tulis Pada Kurikulum Merdeka Di MI NW 1 Kembang Kerang - Husairi, Husairi (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
Literacy skills possessed by children can affect social-emotional development, cognitive development and children's language development. To realize literacy skills in reading and writing, efforts must be made by the teacher council. In this case the researcher used descriptive qualitative research with data collection techniques in the form of observation, documentation and interviews, with data analysis techniques in the form of data triangulation. With the aim of knowing the efforts made by the teacher council in building literacy literacy, the results of the research are: Creating a Class Library or Reading Corner, to build or form a soul that loves reading and writing, madrasas make reading corners or class libraries in all classes, from class I to class VI. Habituation of Literacy in Reading and Writing Before the Learning Process, before starting the learning process, the teacher council before starting to enter the core material to be taught is required to first do literacy literacy. Selection of Learning Media.